Вплив тиску на перколяцiйну поведiнку систем на основi полiетиленоксиду та вуглецевих нанотрубок - Lysenkov, E. A.; Klepko, V. V. (Publishing house "Academperiodika", 2019)
The percolation behavior of systems based on polyethylene oxide and carbon nanotubes (CNTs) and its dependence on the external pressure in the interval from 0.1 to 150 MPa have been studied,by using the method of impedance spectroscopy. As the external pressure grows, the percolation threshold is found to decrease from 0.3% to 0.14%, with the critical index of conductivity changing from 1.95 to 2.73. The change of critical indices testifies to a structural rearrangement of CNTs in the polymer matrix from their statistical distribution to compact aggregates. The experimental results are described well in the framework of the modified McLachlan model, which considers the dependence of the percolation threshold on the pressure.